2014
DOI: 10.1007/s12144-014-9259-9
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict Mediates the Association Between Job Demands and Life and Job Satisfaction in Chinese Middle-Level Managers

Abstract: The present study examined the mediating effect of work-family conflict on the relationships between job demands, life satisfaction and job satisfaction, and the moderating effect of psychological capital on the relationship between job demands and work-family conflict in the Chinese context. Two hundred and fifty middle-level managers from Chinese state-owned enterprises were recruited to complete a battery of self-report measures of work demands, work-family conflict, psychological capital, life satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Finally, respondents were assured that there were no right or wrong answers to items in the questionnaires. Similar high response rates are also reported in extant research (Gao and Jin, 2015;Liu et al, 2014;Michel et al, 2013).…”
Section: Sample and Proceduressupporting
confidence: 85%
See 1 more Smart Citation
“…Finally, respondents were assured that there were no right or wrong answers to items in the questionnaires. Similar high response rates are also reported in extant research (Gao and Jin, 2015;Liu et al, 2014;Michel et al, 2013).…”
Section: Sample and Proceduressupporting
confidence: 85%
“…WFC and FWC each contained five items. Again congruent with an empirical study conducted in Romania (Karatepe, 2013a) and various empirical studies conducted in other countries (Gao and Jin, 2015;Green et al, 2011;Karatepe and Baddar, 2006), WFC and FWC were measured by a five-point scale that ranged from 5 (strongly agree) to 1 (strongly disagree).…”
Section: The Measuring Instrumentsmentioning
confidence: 85%
“…To test the Hypotheses, AMOS 18.0 and SPSS 21.0 were used as statistical tools. In order to deflate measurement errors derived from multiple items for the latent variable, the method of parceling was used (Gao & Jin, 2015). For calling, psychological capital, and work-to-family enrichment, three, four, and three parcels were created, respectively, based on the number of subfactors.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the consequences of work–family conflict, many studies have found that work–family conflict is significantly associated with lower levels of job satisfaction (Allen, Herst, Bruck, & Sutton, 2000; Kossek & Ozeki, 1998). In terms of the mediating role of work–family conflict, past literature examined the mediating effect of work–family conflict in the relationship between job demands and job satisfaction (Gao & Jin, 2015) and the association between supervisor support and job satisfaction (Thomas & Ganster, 1995). In conclusion, it is possible that work–family conflict is a key variable to mediate the relationship between the Job Demands–Control–Support model variables and employees’ job satisfaction.…”
Section: Theoretical Backgroundmentioning
confidence: 99%